Q. 173.5( 6 Votes )

# Find the remainde

Answer :

If we divide f(x) = 4x^{2} - 12x^{2} + 14x - 3 by (2x - 1) remainder can be find at value of –

(2x-1) = 0

Or x = 1/2

So, we will put x = 1/2 in f(x) = 4x^{2} - 12x^{2} + 14x – 3

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

In each of the foRD Sharma - Mathematics

In each of the foRD Sharma - Mathematics

When (x^{31</s}RS Aggarwal & V Aggarwal - Mathematics

Find the remaindeRS Aggarwal & V Aggarwal - Mathematics

When p (x) = (x<sRS Aggarwal & V Aggarwal - Mathematics

If p (x) = 2x<supRS Aggarwal & V Aggarwal - Mathematics

If (x^{3}RS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

When p (x) = x<suRS Aggarwal & V Aggarwal - Mathematics

(x +1) is a factoRS Aggarwal & V Aggarwal - Mathematics